PROPOSED MARKETING STRATEGY TO IMPROVE PURCHASE INTENTION IN EVENT INDUSTRY: CASE STUDY OF ELDORADO DOME - Ardhianty, Devina Alifia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Eldorado Dome is a versatile event venue in Bandung, accommodating various large-scale events such as weddings, exhibitions, corporate gatherings, and MICE (Meetings, Incentives, Conferences, and Exhibitions). Its strengths include substantial capacity, advanced technical infrastructure, and ample parking, offering significant value to event organizers, wedding planners, and corporate clients. Despite these advantages, challenges related to location accessibility, limited promotional efforts, and competition from centrally located venues persist. This study examines the influence of the 7P marketing mix—product, price, place, promotion, people, process, and physical evidence—on purchase intention. Results indicate that all elements positively affect customer intentions. To address identified challenges, three strategic initiatives are proposed: positioning Eldorado Dome as a premier event venue by highlighting its parking and premium amenities; establishing its status as a leading MICE venue through targeted industry engagement and partnerships; and enhancing digital marketing strategies, including SEO and social media campaigns, to increase visibility and attract a broader audience. These strategies aim to strengthen Eldorado Dome's market presence, meet stakeholder needs, and solidify its position as a leading event venue in Bandung.